(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Proteus mirabilis a Gram-negative bacteria belonging the Enterobacteriaceae family and that causes several infections to patients such as urinary tract infections, middle ear infections, wounds and burns, in addition to other infections. This study aimed to isolate and diagnose Proteus mirabilis bacteria collected from different samples of infection sources from patients present in many hospitals using traditional diagnostic like morphological and biochemical tests as well as molecular methods. The Identification system for Gram negative bacteria GN24 KIT had used to detect Proteus mirabilis species . The results of using this kit were confirmed by the molecular diagnosis of bacteria through the PCR technique of the 16S rRNA gene, where the confirmation rate was 100%. The PCR sample was analyzed in Macrogen Corporation–Korea for Sanger sequencing using ABI3730XL, an automated DNA sequences. the findings were obtained and analyzed via genius software in order to Synthesis of the phylogenetic tree of the isolated strains that resulted from the discovery of a new global strain of Proteus mirabilis bacteria and was recorded in NCBI genebank with accession number (MN 700085) and name (M.K.84 ).